Anthropometric assessment protocol in Aesthetic Nutrition and Women's Health (Research, Society and Development, 2024)
In nutritional assessment aimed at women's aesthetics and health, double indirect methods are the most effective for baseline analysis, diagnosis and monitoring of body composition. Among these methods, anthropometry stands out, which, through the measurement of parts of the body, using different techniques (adipometry, perimetry, etc.) allows a global and/or localized assessment. In Brazil, the adult female population has higher rates of overweight and obesity than males. In addition to the potential aesthetic problem arising from excess body mass, it also increases the risk of developing cardiovascular diseases, type 2 diabetes mellitus and cancer. Despite the alarming numbers and associated problems, there is a lack of anthropometric protocols, which are characterized by ease, speed, reproducibility, low cost, acceptance and synergism among health professionals in the scientific literature. This article aims to present the adaptation and evolution of a care protocol for assessment of aesthetics and women's health, to fill a fundamental gap in nutritional care and various specialties in the area of women's health and aesthetics.